A professional nurse's understanding of quality nursing care in Limpopo province, South Africa - Maggie Nyelisani; Lufuno Makhado; Takalani Luhalima (AOSIS, 2023)
Background: Quality has increasingly become a critical part of life in every aspect. Patients are today continuously looking for good quality services from health professionals. Professional nurses are expected to render quality care to fulfil the patients' healthcare needs. Poor nursing care has led to several litigations and the loss of patients' lives. It is essential to explore professional nurses' viewpoints regarding quality nursing care. Objectives: To explore and describe the understanding of professional nurses regarding quality care rendered to patients in the selected hospitals of Limpopo Province. Method: This study utilised a qualitative, exploratory-descriptive design. Individual semi-structured interviews were conducted for data collection. Participants comprised 35 professional nurses who were purposely selected. Data collected were audio-recorded and transcribed verbatim. Data were analysed using Tech's eight-step data coding process, which led to the emergence of themes and sub-themes. Trustworthiness was ensured through credibility, confirmability, dependability, and transferability. Results: Three themes emerged: professional nurses' descriptions, meanings, and expectations of quality nursing care. The findings highlight that quality nursing care means meeting patients' needs through advocacy, empathy, fulfilment of patients' needs, good interpersonal relationships and teamwork. Challenges experienced included the lack of resources and staff shortage. Conclusion: Hospital management needs to develop effective ways to support professional nurses in delivering quality nursing care. In discussion with the Department of Health (DoH), hospitals should be fully equipped with resources to render quality care to patients. Evaluation of service quality and patient satisfaction should be ongoing for improving the quality of patient care. Contribution: The study reveals that professional nurses perceive quality nursing care differently. Moreover, it emphasises the importance of maintaining and promoting quality nursing care as the cornerstone of healthcare.